ANALISIS FAKTOR PENDUKUNG DAN PENGHAMBAT PENGELOLAAN ATRAKSI WISATA AIR MANCUR SRI BADUGA - Muhamad Nur Alfi Syahrin; Poni Sukaesih Kurniati (Journal of Tourism and Economic, 2020)
The purpose of this study is to identify the supporting and inhibiting factors of the management of the Sri Baduga Fountain Park, Purwakarta Regency. The method used in this research is descriptive with a qualitative approach, data models used is by literature studies, to test the validity of the data is done through triangulation, while for data analysis is done through an interactive model. The results showed that the supporting factors in the management of the Sri Baduga Fountain Park tourism object consisted of: entertainment concept factors; The factor of application of Sundanese culture; and marketing factors, as for the inhibiting factors of the Sribaduga Fountain Park tourist attraction, including the condition of the supporting facilities; Water resource factor; and management funding factors. Researchers recommend that DISPORAPARBUD Purwakarta Regency be able to evaluate the concept of funding tourist attraction facilities; looking for water management concepts; and socializing the importance of implementing ticket-based payments and/or charges at Sri Baduga Fountain Park.